Conexão florestal em áreas mais favoráveis à infiltração na APA Botucatu-SP - Souza, Paula Oddone [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The replacement of natural landscapes for agricultural crops has compromised the quantity and quality of habitat among species due fragmentation of forest regions. The connection of these patches is essential to maintain gene tic flow between populations and consequently the security of the species. Preservation Areas (PA) were established with the objective of preserving the relevant areas for conservation of biodiversity and natural resources. The Environmental Protection Are a Botucatu belongs to sustainable use category of PA, which was consolidated in 1983 and has significant natural attributes such as the Basaltic Cuesta, recharge areas of the Guarani Aquifer System, an important source of groundwater, in addition to remai ning native vegetation and the local wildlife. However, its management plan is not in effect, compromising the preservation of natural resources and biodiversity. Therefore, this paper established priority areas for forest connection between the most impor tant patches for landscape connectivity located EPA Botucatu, prioritizing areas more favorable to infiltration using geoprocessing techniques. The most favorable to infiltration and percolation to groundwater supply areas were obtained from five factors t o compose the Weighted Linear Combination (WLC) , which were: geology, type of soil, slope , geomorphology , land use. Those areas areas were then overlaid by the priority areas for landscape connectivity, obtained through the Integral Index of Connectivity, resulting on the map with the priority areas for connection of landscape fragments. It was observed that the choice of method is feasible to establishment of priority areas for forest connection in areas that promote infiltration and the five factors adopt ed for the WLC were important to delimit the most favorable to infiltration and groundwater supply areas . The information generated from this study will enable ...

A substituição de paisagens naturais por culturas agrícolas tem comprometido a quantidade e qualidade de habitat de diversas espécies , por meio da fragm entação dos maciços florestais e sua conexão é essencial para manter o fluxo gênico entre as populações e , consequentemente , a segurança das espécies . As unidades de conservação (UC) foram constituídas com o o bjetivo de preservar as áreas relevantes para conservação da biodiversidade e dos recursos naturais. A APA Botucatu trata - se de uma UC de uso sustentável, cuja consolidação data de 1983 e possui importantes atributos naturais como as Cuestas Basálticas, as áreas de recarga do Sistema Aqu ífero Guarani , importante manancial de água subterrânea, além dos remanescentes de vegetação nativa e a fauna local. Contudo , seu plano de manejo não se encontra em vigência, podendo comprometer a preservação dos recursos na turais e da biodiversidade . Desse modo , este trabalho estabeleceu áreas prioritárias para conexão florestal entre os fragmentos mais importantes para a conectividade da paisagem da APA Botucatu, priorizando áreas mais favo ráveis à infiltração , por meio de técnicas de Geoprocessamento. As áreas mais favoráveis à infiltração e percolação para abastecimento do lençol fre ático foram delimitadas por meio de cinco fatores para compor a Combinação Linear Ponderada e s ão eles: geologia, pedologia, declividade, formas do terreno e uso do solo. As áreas resultantes foram então sobrepostas aos fragmentos prioritários para a conectividade ...
Keywords: Recursos naturais - Conservação; Áreas de conservação de recursos naturais; Infiltração; Geoprocessamento; Water resources development